Optimizing Dam Maintenance: An Integrated BIM-WBS Operational Model - Fitria, Diana Rohmatul; Latief, Yusuf; Saleh, Toha; Laksono, Naufal Budi (Journal of Project Management Research, 2025)
This study addresses the challenges of inefficient dam maintenance by proposing and validating an integrated operational model that leverages Building Information Modelling (BIM) and Work Breakdown Structure (WBS).  Traditional dam maintenance often suffers from poor coordination, inadequate resource allocation, and scheduling delays. To overcome these limitations, this research developed a novel model that seamlessly integrates BIM's 3D visualization and data management capabilities with the hierarchical structure of WBS.  A mixed-method approach, combining literature review, expert validation, and a case study application, was employed to develop and evaluate the model.  The resulting operational model demonstrated improved task efficiency, resource optimization, and stakeholder collaboration through real-time task tracking, streamlined workflows, and enhanced prioritization of maintenance activities. Expert feedback confirmed the model's practicality and effectiveness in resolving common maintenance issues, highlighting its potential to improve communication, reduce delays, and increase the accuracy of maintenance planning. The validated BIM-WBS integrated model provides a robust framework for enhancing dam maintenance performance, offering data-driven decision-making and improved stakeholder collaboration. Future research directions include exploring the model's applicability to other infrastructure types and integrating real-time technologies like IoT and AI for predictive maintenance capabilities.